Qualitative Study : Factors Influencing Learning Motivation Of Final Year Students In The Tutorial Process In Faculty of Medicine Lampung University - Thoriq Aziz; Dwita Oktaria; Oktafany (Medula, 2020)
Learning motivation is important in the learning process, especially in a problem-based learning discussion or tutorials that require high learning motivation to achieve learning goals. Lerning motivation in a tutorial is influenced by a variety of factors both internal and external. Learning motivation of final year students decreased, especially during the tutorial process. This study uses a qualitative research design with a phenomenological approach. The main informants in this study were students from the class of 2015 as final year students. Data Collection through Focus Group Discussion (FGD), then the researchers also used in-depth interview techniques as data triangulation. Research data were analyzed by thematic analysis. The results of the study found various factors that influence the motivation of students learning at the final level of Faculty of medicine Lampung University in the tutorial process. We found five internal factors that increase student motivation in the tutorial process, i.e the level of intelligence, ideas, the desire to graduate immediately, the will of oneself, and the ability to communicate well. Then we found five internal factors that decrease student motivation in the tutorial process, i.e decreased health conditions, lazyness, bored, lacking self-readiness. For external factors we found five external factors that can increase or decrease student learning motivation in the tutorial process, i.e facilitators, learning materials, facilities and infrastructure, parental support and learning environtment. Then we found another one external factors that increase student motivation in the tutorial process, i.e scenarios. Then we found two external factors that reduce student motivation in the tutorial process i.e academic burden and the influence of friends.